Effect of Blended Cement Containing Fly Ash on the Elastic Modulus and Poisson's Ratio of Mortar - Maysyurah, Alfina; Aris, Mohammad; Fajar, Muhammad Nur; Arifin, Herlina; Setya, Didik (Universitas Islam 45, 2025)
The demand for eco-friendly, economical, and high-performance building materials continues to grow, encouraging innovation in the use of blended cement. Fly ash, a by-product of coal combustion, offers a sustainable alternative as a supplementary cementitious material. This study evaluates the mechanical performance of mortar containing fly ash in blended cement, with compressive strength tested at 7, 28, and 90 days. Fly ash proportions of 0%, 10%, 20%, 30%, and 40% by cement weight were examined. Results showed that mortar with fly ash (FA-10%) achieved the highest compressive strength at 90 days. Although the elastic modulus decreased with higher fly ash content, both compressive strength and elastic modulus increased over the curing period. The Poisson’s ratio values ranged from 0.1 to 0.3, indicating the material remains within the classification of normal solid materials. These findings suggest that incorporating fly ash can improve the sustainability of construction materials without significantly compromising long-term mechanical performance. Fly ash can therefore be considered an effective partial replacement for cement in efforts to develop more environmentally responsible and sustainable building solutions.